2020
DOI: 10.21037/tlcr.2020.04.17
|View full text |Cite
|
Sign up to set email alerts
|

Predicting EGFR mutation subtypes in lung adenocarcinoma using 18F-FDG PET/CT radiomic features

Abstract: Background: Identification of epidermal growth factor receptor (EGFR) mutation types is crucial before tyrosine kinase inhibitors (TKIs) treatment. Radiomics is a new strategy to noninvasively predict the genetic status of cancer. In this study, we aimed to develop a predictive model based on 18 F-fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-FDG PET/CT) radiomic features to identify the specific EGFR mutation subtypes.Methods: We retrospectively studied 18 F-FDG PET/CT images of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 54 publications
3
53
2
Order By: Relevance
“…The statistical analysis of the ROC curve showed that a maximum tumour diameter of 35 mm was the cutoff point, and tumours with smaller diameters (≤35 mm) had a higher EGFR mutation rate than those with larger tumours, which is consistent with previous ndings [25]. The results of this study suggest that patients with stage IV disease according to the TNM staging guidelines have a higher mutation rate, which is inconsistent with previous research [26], but the number of cases was small, and there may have been selection bias. Finally, univariate analysis showed that the EGFR mutation rate in non-smokers was higher than that in smokers which is consistent with another study [27,28].…”
Section: Discussioncontrasting
confidence: 59%
“…The statistical analysis of the ROC curve showed that a maximum tumour diameter of 35 mm was the cutoff point, and tumours with smaller diameters (≤35 mm) had a higher EGFR mutation rate than those with larger tumours, which is consistent with previous ndings [25]. The results of this study suggest that patients with stage IV disease according to the TNM staging guidelines have a higher mutation rate, which is inconsistent with previous research [26], but the number of cases was small, and there may have been selection bias. Finally, univariate analysis showed that the EGFR mutation rate in non-smokers was higher than that in smokers which is consistent with another study [27,28].…”
Section: Discussioncontrasting
confidence: 59%
“…In a study with 248 lung cancer patients without treatment, researchers found that their model for prediction of EGFR mutations could reach an AUC of 0.87 when combined clinical and radiomic signature [105]. Similar performance has also been reported in another retrospective study [106]. In addition, for patients with EGFR mutation, a deep radiomic score was a non-invasive tool to identify NSCLC patients susceptible to tyrosine kinase or immune checkpoint inhibitors [107].…”
Section: Applications Of Functional Radiomic Features In Lung Cancersupporting
confidence: 55%
“…Only GLCM_DV from PET images, which measures the heterogeneity of different intensity-level matrix, showed significant but unsatisfactory predictive performance in our study (AUC=0.661). Liu Q, et al recent study ( 35 ) established a predictive model for EGFR mutation subtypes using machine learning algorithm, which seemed to have better classification performance (AUC=0.77 and 0.92 for respectively predicting exons 19 del and 21 L858R mutations) than ours. However, the number of exons 19 del and 21 L858R mutations was small in Liu Q’s study (only 44 and 31 cases respectively), especially when divided as the train and test cohorts, so the generalization ability of the predictive model was not clear.…”
Section: Discussionmentioning
confidence: 63%